Salvador Allende : revolutionary democrat - Figueroa Clark, Victor (Revolutionary Lives, 2013)
This is a political biography of one of the 20th century’s most emblematic left-wing figures - Salvador Allende, who was president of Chile until he was ousted by General Pinochet in a US-supported coup in 1973. Victor Figueroa Clark guides us through Allende's life and political project, answering some of the most frequently asked questions. Was he a revolutionary or a reformist? A bureaucrat or inspirational democrat? Figueroa Clark argues that Allende and the Popular Unity Party created a unique fusion which was both revolutionary and democratic. The process led by Allende was a symbol of hope for the left during his short time in power. Forty years on, and with left governments back in power across Latin America, this book looks back at the man and the process in order to draw vital lessons for the left in Latin America and around the world today.